MO739: Evaluation of a Capillary Blood Potassium Measurement Method in Healthy Volunteers and in Chronic Haemodialysis Patients. (3rd May 2022) - Gruson, Damien; Jadoul, Michel; Deltombe, Matthieu; Nevraumont, Arnaud; Berenger, Maurice; Lefebvre, David; Henrion, Guilhem; Papillon, Julie; Rossignol, Patrick
Abstract: BACKGROUND AND AIMS: Potassium monitoring is recommended by guidelines in patients with cardiorenal disease, at the risk of life-threatening dyskalemia, and yet poorly implemented in daily practice. CardioRenal is developing a method allowing patients with chronic cardiovascular/chronic kidney disease to self-monitor potassium from home whilst using capillary blood samples. The aim of this study (NCT04907773) was to evaluate the feasibility of potassium measurements with a new point-of-care device developed by CardioRenal, ultimately designed for self-monitoring. METHOD: This was an open, prospective, monocentric study in adult healthy volunteers (HV) and in chronic haemodialysis (HD) patients. The latter were either recruited pre-dialysis, after a long interdialytic interval and presenting with a K + > 5.0 mmol/L just before starting their HD session, or post-dialysis, in patients treated with a 2 mmol/L dialysis bath and presenting with a K + < 3.5 mmol/L at the end of the HD session. Potassium screening check was performed on venous (vein or central catheter) or arterio-venous (fistula) blood samples using the iSTAT TM . Additionally, as a reference, an (arterio)venous blood collection was performed. Potassium concentrations were measured with the CardioRenal device, using a proprietary methodology, in <10 µL capillary blood drawn, by a healthcare professional, using the Tasso + TM device, and compared with the gold standard (venous) plasma potassium (ROCHE Cobas) or predicate (whole blood iSTAT TM ). The pre-specified test acceptance rules were (i) 95% of the samples of CardioRenal measurement potassium concentration will be at target value ±0.5 mmol/L (which means that total error is <0.5 mmol/L (IC95) and (ii) in case of absolute bias >0.5 mmol/L and <0.5 mmol/L induced by capillary sampling and/or comparative method (iSTAT TM or central lab) respectively, standard deviation of the difference distribution is <0.25 mmol/L (i.e. 95% CI < 0.5 mmol/L). The sample size was calculated as recommended in performance evaluation guidelines (CLSI, Westgard) to allow for a good estimate of the bias between the two measurement procedures and the estimates for bias, at any concentration. A total of 70 subjects was needed to generate 100 paired capillary/venous blood samples to compare the candidate device to the gold standard. Statistical methods were mainly Bland–Altman standard deviation analyses and Passing–Bablock correlations. RESULTS: A total of 88 participants were screened and 63 [M/W: 43/57%; mean age 46.3 years (extremes 21–91); HV/HD: 38/25] met the study requirements and were analysed. The plasma potassium measurements (Roche Cobas), from venous or arterio-venous samples, were as follows: mean 4.28 mmol/L, median 4.05 mmol/L, SD 0.91 mmol/L (2.86–7.12 mmol/L). The standard deviations observed with Bland–Altman analyses (0.28 mmol/L for Capillary Cardiorenal versus Venous iSTAT and 0.25 mmol/L for Cardiorenal Capillary versus Plasma Central Lab) fulfilled the acceptance rules for the CardioRenal method. The observed Passing–Bablock correlations displayed an R 2 = 0.9115 and an R 2 = 0.9266, respectively (Fig. 1 ) . CONCLUSION: These preliminary data demonstrate the feasibility and the reliability of measuring potassium concentrations in capillary blood with the combined use of the Tasso TM capillary sampling device and the new CardioRenal potassium measurement device, as compared with the gold standard potassium measurements in venous samples. This new, potentially disruptive method will be further developed for potassium self-monitoring at home, in patients at risk of dyskalemia.